An investigation into inflammasome-gene expression profile and genome-wide genotype data in gout - Sandoval-Plata, Gabriela (2022)
Background: Gout is the most common form of inflammatory arthritis, with a prevalence of 2.49% in the United Kingdom. It is characterised by episodes of acute inflammation (flares) caused by shedding of monosodium urate (MSU) crystals that deposit within and around joints when serum urate (SU) increases above its solubilisation point. Despite the central role of hyperuricaemia in the pathogenesis of gout, not everyone with elevated SU develop symptomatic gout. The reasons underlying the transition from asymptomatic hyperuricaemia, with our without MSU crystal deposits, to symptomatic gout remain poorly understood.